Study of Supply Chain Selection Strategies of Firms under Geopolitics - Xi, Haonan; Xu, Zhihao; Yao, Jingwen; Li, Song; Yang, Xiao (International Journal of Social Sciences and Public Administration, 2024)
Based on the geopolitical perspective, the study analyzes the interaction between global trade policies and supply chain strategies, and constructs a theoretical model to explore how the tariff structure of final products is shaped by value-added content and the role of the most-favored-nation (MFN) rule and the principle of reciprocal trade in it. The findings suggest that geopolitical factors have a significant impact on international trade strategies and supply chain configurations. This theoretical framework indicates the importance for policymakers to consider geopolitical complexity in maintaining the global trade order and supply chain resilience, and promotes the construction of solid and adaptable international trade and supply chain management strategies.